ANALISA KINERJA KEUANGAN HOTEL PADA HOTEL SAHID KAWANUA MANADO - Kakinsale, Efafras Juan; Karamoy, Herman; Elim, Inggriani (Universitas Sam Ratulangi, 2020)
This study aims to determine and analyze the hotel financial performance of 2017-2018 at the Sahid Kawanua Manado hotel by using Liquidity analysis (the company's ability to meet its short-term obligations), Solvency (the extent to which the company's ability to meet its long-term obligations), and Profitability analysis (looking at the ability the company generates profit) the effect of profitability, liquidity, and solvency on the soundness of the company, the soundness of the company is needed to determine whether the company's financial condition is healthy or not. This can be done by comparing the ratio of the previous year with the current ratio with analysis of liquidity ratios shows how much the company's ability to use its capital to generate profits in a certain period.